Algorithm for Screening of Adrenal Function in Stable Patients with Cirrhosis - Paz Delgadillo, Jonathan; Monreal Robles, Roberto; Villarreal Pérez, Jesús Zacarías; Lavalle González, Fernando Javier; Maldonado Garza, Héctor Jesús; Bosques Padilla, Francisco Javier (Ediciones Medicina y Cultura, 2017)
Introduction and aims. AI) is common in patients with cirrhosis. We aimed to assess the presence of AI in stable patients with cirrhosis using the gold-standard insulin tolerance test (ITT) and to propose an algorithm for screening AI in these patients. Material and methods. We studied 40 stabl Material and methods. e patients with cirrhosis. We determined the basal total (BTC) and peak cortisol (PTC) levels. Using the ITT, we defined AI as a serum PTC < 18 Pg/dL at 30 min after insulin-induced hypoglycemia. We assessed the diagnostic accuracy of BTC in different stages of liver disease to discriminate between those with NAF and AI. Results. Of the 40 patients, 24 (60%) presented with AI. Child-Pugh and MELD scores differed between the NAF and AI groups Results. (Child-Pugh: NAF 7.2 r 1.7 vs. AI 8.8 r 2.4, p = 0.024 and MELD: NAF 9.9 r 2.5 vs. AI 14.9 r 6.3, p = 0.001). The BTC level was lower in patients with AI than in those with NAF (7.2 r 2.4 vs. 12.5 r 5.2, p < 0.001). A BTC value d 10.0 Pg/dL had a 96% sensitivity (negative predictive value: 90%) for identifying AI. This cutoff value (BTC d 10.0 Pg/dL) provided 100% specificity (positive predictive value: 100%) in patients with advanced liver disease (Child-Pugh t 9 or MELD t 12). Conclusion. An algorithm in- Conclusion. cluding the use of BTC and the severity of liver disease may be a useful and simple method for assessing adrenal function in stable patients with cirrhosis.